Sand-Clay Mix in Phosphate Mine Reclamation: Characteristics and Land Use - Casey Beavers; Edward A. Hanlon; Matt Wilson; James Cates; George J. Hochmuth (EDIS)
Phosphate rock is a key component in producing fertilizer and many other economically important products. Getting phosphate rock out of the ground produces a by-produce called phosphate clay, which mining operations must return to the landscape. However, phosphate clay retains large amounts of water, making them unsuitable for use as farmland or wildlife habitat. This 6-page fact sheet explains how using a sand-clay mix can more efficiently restore the landscape and put it to beneficial use. Written by Casey Beavers, Edward A. Hanlon, Matt Wilson, James “Bud” Cates, and George J. Hochmuth, and published by the UF Department of Soil and Water Sciences, July 2015.